2020
DOI: 10.1016/j.redox.2019.101422
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin K inhibition-induced mitochondrial ROS enhances sensitivity of cancer cells to anti-cancer drugs through USP27x-mediated Bim protein stabilization

Abstract: Cathepsin K (Cat K) is expressed in cancer cells, but the effect of Cat K on apoptosis is still elusive. Here, we showed that inhibition of Cat K sensitized the human carcinoma cells to anti-cancer drug through up-regulation of Bim. Inhibition of Cat K increased USP27x expression, and knock down of USP27x markedly blocked Cat K-induced up-regulation of Bim expression. Furthermore, inhibition of Cat K induced proteasome-dependent degradation of regulatory associated protein of mammalian target of rapamycin (Rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 59 publications
1
39
0
Order By: Relevance
“…It can further activate downstream products of the eIF4 complex to promote tumor development, regulate the cell cycle, and inhibit autophagy and apoptosis [ 19 ]. Seo et al [ 25 ] demonstrated that inhibition of mTOR enhanced the chemosensitivity of cancer cells. They also revealed that treatment with mTOR inhibitors reduced tumor size and increased apoptosis in a xenograft model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can further activate downstream products of the eIF4 complex to promote tumor development, regulate the cell cycle, and inhibit autophagy and apoptosis [ 19 ]. Seo et al [ 25 ] demonstrated that inhibition of mTOR enhanced the chemosensitivity of cancer cells. They also revealed that treatment with mTOR inhibitors reduced tumor size and increased apoptosis in a xenograft model.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CTSK -KD significantly decreased levels of p-mTOR and p-mTOR/mTOR, which inhibited activation of the mTOR signaling pathway. Previous studies have demonstrated that inhibition of Cathepsin K can induce proteasomal degradation of proteins associated with regulatory mechanisms on the target of rapamycin [ 25 ]. This conclusion is inconsistent with our experiment, which suggests that Cathepsin K may play a role in NSCLC through regulation of the mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze DNA fragmentation, we used death detection ELISA plus kit (Boehringer Mannheim, Indianapolis, IN, USA) according to the manufacturer’s recommendations. To measure DEVDase activity, cells were treated with IITZ-01 and/or TRAIL, harvested, and incubated with reaction buffer containing acetyl-Asp-Glu-Val-Asp p-nitroanilide (Ac-DEVD-pNA) substrate, as previously mentioned [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…The assay was performed as described in our previous study [ 45 ]. Cells were co-transfected with HA-tagged ubiquitin (HA-Ub), USP9X/wild type and UPS9X/C1566S plasmid, and treated with MG132 for 12 h. Immunoprecipitation was performed using the anti-survivin, and ubiquitination of endogenous survivin was checked using HRP-conjugated anti-Ub under denaturing conditions.…”
Section: Methodsmentioning
confidence: 99%